TEACHER'S POSITION TO INTERPERSONAL INTERACTION IN A CONFLICT SITUATION (Pedagogy of Higher and Secondary Education, 2010)
In the article grounds possibilities of the position of teacher to interpersonal interaction in the conflict situation.
Keywords: interpersonal interaction; conflict situation; position teacher